Introduction : The Aftermath of Civil War - Elbadawi, Ibrahim (2012)
This article introduces the special issue on 'The Aftermath of Civil War' and presents the research project from which the articles in this issue originate. The article presents a few empirical observations that demonstrate the increasing importance of the post-conflict situation for actors that engage to reduce the global incidence of armed conflict. The global incidence of conflict was reduced from 1992 to 2002, since there were more terminations than onsets. Although this trend seems to have halted, a scrutiny of the onsets shows that they increasingly are recurrences of conflicts that have been inactive for a period. In 2005 and 2006, there were no new conflicts. The article then briefly introduces the six contributions to the special issue. The articles investigate the importance of peacekeeping troops, elections, aid, capital flight, and exclusion of parties from peace agreements in post-conflict situations. The articles are also applicable to countries that have not had armed conflicts, as the authors investigate the relationship between ethnic diversity and military spending and the determinants of youths' decisions to participate in rebel groups.